Tutorial: Luminance Maps for Daylighting Studies from High Dynamic Range Photography. Issue 2 (3rd April 2021) - Pierson, C.; Cauwerts, C.; Bodart, M.; Wienold, J.
ABSTRACT: In the field of lighting, luminance maps are often used to evaluate point-in-time lighting scenes from the occupant's vantage point. High Dynamic Range (HDR) photography can be used to generate such luminance maps. The aim of this tutorial is to present a comprehensive overview of a step-by-step procedure to generate a 180° luminance map of a daylit scene from a sequence of multiple exposures with semiprofessional equipment and the Radiance suite of programs. The procedure consists in capturing a sequence of multiple exposures of the visual scene; selecting the useful exposures; merging the exposures to generate the HDR image by using the predefined camera response function; nullifying the exposure value; resizing and cropping the HDR image by using the predefined fisheye view coordinates; adjusting the projection of the HDR image by using the predefined distortion function; correcting the vignetting of the HDR image by using the predefined vignetting curves; correcting the alterations of the HDR image due to the Neutral Density (ND) filter if one was used, by using the predefined ND correction function; adjusting the photometry of the HDR image by using the measured spot luminance value; editing the HDR image header by using the predefined projection type and real viewing angle; and checking the validity of the HDR image by using the measured vertical illuminance, and, if needed, the predefined luminous range. To conclude, an analysis of errors is made and attention points to adapt the procedure for electric or circadian lighting studies are discussed.